Law, Jan (audio interview #3 of 4) - Law, Jan (1/25/1908 - 1/27/1994); Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - Law's third interview was conducted following a tour of "Bixby A Lease." It is in a wetland that, other than the oil production activity, is undeveloped and serves as a wildlife refuge. Law drove Briegel around and showed her birds and other wildlife th 11/4/1983